ANALISIS KONDISI MENSTRUASI ATLET SEPAKBOLA PUTRI KABUPATEN SUKABUMI BERDASARKAN KONDISI FISIK, PSIKOLOGIS, DAN PERFOMA LATIHAN - Ilpana Samiyasa; Iqbal Fajarullah; Rafdlal Saeful Bakhri (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
The menstrual cycle is a physiological factor that often affects the physical, psychological, and motor performance of female athletes during training. This study aims to compare the physical performance and endurance of female soccer athletes during each menstrual cycle (day 1 to day 6). This is a quantitative study using a descriptive comparative method. The sample consisted of 15 athletes from the Sukabumi Regency Women's Soccer Team, selected using a purposive sampling technique. The data collection instrument used a structured observation sheet based on a Likert scale (1–4), which measured physical, psychological, and training performance indicators during the six days of menstruation. Data analysis was conducted using quantitative descriptive analysis to determine trends in the development of average daily scores. The results showed a significant decline in performance at the beginning of menstruation. Day 2 of menstruation was the lowest point for athletes, with an overall average score of 2.64, driven by high levels of abdominal pain/cramps (2.27) and decreased mood (2.33). The deepest decline in motor performance occurred in speed and reaction time on day 3, with the lowest score being 1.80. Meanwhile, endurance parameters experienced a drastic decline on day 2 (2.27) and only returned to optimal levels on day 6 (3.75). Overall, the athletes' physical and psychological performance gradually recovered and reached peak condition on day 6 with an average total of 3.83. The conclusion of this study is that the menstrual cycle negatively affects the endurance and training performance of female athletes, especially on days 1 to 3, so adaptive training program adjustments are needed by coaches.